Does age matter? Impact on fire safety properties of composite materials from ageing. Issue 1 (October 2020) - Sandinge, Anna; Blomqvist, Per; Dederichs, Anne
Abstract: When materials are tested and classified before entering the market, they are mainly tested as newly produced. However, it is known that material properties change with time and when exposed to temperature, humidity, wind and light. As a result, it is important to have knowledge of how material age and which parameters are affected in order to retain safety. Studies show how the mechanical properties change when the materials age. But not much can be found in literature about the ageing effect on fire properties. In the present study, accelerated ageing testing was made with a composite material of phenolic resin and basalt fibres. Selected ageing methods applied were thermal ageing at 90 °C and moisture ageing at 40 °C and 90 % Relative Humidity. Samples were collected from ageing chambers after one, two and four weeks. To investigate the ageing effect on the fire properties of the composite, fire testing was conducted using cone calorimetry according to ISO 5660-1. The test results showed that ageing does matter. There was an impact on the material and the fire properties were affected. The ignition time decreased for the aged samples and the heat release rate slightly increased. Also, the smoke production increased with ageing.